Is There a Role for Diabetes-Specific Nutrition Formulas as Meal Replacements in Type 2 Diabetes? - Noronha, Jarvis C.; Mechanick, Jeffrey I. (Frontiers in Endocrinology, 2022)
Nutrition therapy plays an integral role in the prevention and management of patients with type 2 diabetes (T2D). A potential strategy is the utilization of diabetes-specific nutrition formulas (DSNFs) as meal replacements. In this article, we distinguish DSNFs from standard nutrition formulas, review the clinical data examining the effectiveness of DSNFs, and propose an evidence-based algorithm for incorporating DSNFs as part of nutrition therapy in T2D. DSNFs contain slowly-digestible carbohydrates, healthy fats (e.g., monounsaturated fatty acids), and specific micronutrients, which provide added benefits over standard nutrition formulas. In short- and long-term clinical trials, DSNFs demonstrate improvements in postprandial glycemic responses translating into sustainable benefits in long-term glycemic control (e.g., hemoglobin A1c and glycemic variability) and various cardiometabolic outcomes. To facilitate the delivery of DSNFs in a clinical setting, the transcultural diabetes nutrition algorithm can be utilized based on body weight (underweight, normal weight, or overweight) and level of glycemic control (controlled or uncontrolled).